1966
DOI: 10.1037/h0022979
|View full text |Cite
|
Sign up to set email alerts
|

Temporal conditioning of GSR.

Abstract: Temporal conditioning (time as CS, shock as UCS) of the GSR was demonstrated in a situation where spontaneous responding, sensitization, reactive inhibition, and time-estimation processes were properly controlled. The nature of "time" as an elicitive stimulus is discussed in terms of stimulus trace and response-produced stimulus cycle concepts both of which are considered inadequate explanations of temporal conditioning. The acquisition and the failure to extinguish the temporal CR pose theoretical problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Based on prior work (Lockhart, 1966; Pendergrass and Kimmel, 1968), UCS presentations at fixed ITIs should support temporal conditioning, while UCS presentations at random ITIs should not. Given this directional hypothesis, UCS expectancy data were included in a 1-tailed paired t-test to determine whether expectation of the UCS differed between temporal conditioning (i.e., fixed ITI) and control (i.e., random ITI) conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on prior work (Lockhart, 1966; Pendergrass and Kimmel, 1968), UCS presentations at fixed ITIs should support temporal conditioning, while UCS presentations at random ITIs should not. Given this directional hypothesis, UCS expectancy data were included in a 1-tailed paired t-test to determine whether expectation of the UCS differed between temporal conditioning (i.e., fixed ITI) and control (i.e., random ITI) conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Prior research has demonstrated temporal conditioning of SCR (Lockhart, 1966; Pendergrass and Kimmel, 1968). Therefore, we expected conditioned SCRs would be greater during temporal conditioning than the control procedure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Timing ofindividual cycle (e.g., Goddard, 1995;Lockhart, 1966;Maes & Vossen, 1992;Pavlov, 1927;Williams, Frame, & LoLordo, 1992) and stimulus (e.g., Baum& Bindra, 1968;Lynch, 1973;Pavlov, 1927;Rescorla, 1967) durations has been reported in a variety of conditioning paradigms. The present results indicate that when both durations are present in the same procedure, they are both timed.…”
Section: Discussionmentioning
confidence: 99%